Impact of the hemoglobin-to-red cell distribution width ratio on 30-day readmission in patients with heart failure - Zhongkai He; Chongzhou Zheng; Menghua Chen; Tao Chen; Fei Huang; Ziliang Zhu; Yuan He; Ming Li (BMC Cardiovascular Disorders)
Abstract Background Predicting all-cause readmission in patients with heart failure (HF) is crucial. This study investigated the independent risk factors for short-term readmission and assessed the potential mediators involved in this process. Methods We evaluated data from 2,254 patients with HF admitted to our institution between January 2019 and December 2020. Logistic regression analysis was used to examine the association between sarcopenia index (SI), neutrophil-to-lymphocyte ratio (NLR), hemoglobin-to-red cell distribution width ratio (HRR), and all-cause 30-d readmission. A restricted cubic spline regression model with three knots assessed potential non-linear relationships between confounders and readmission risk. A mediation analysis was performed to evaluate the direct and indirect effects, as well as the proportion of mediation. Results The mean age of the participants was 72 ± 12 years, with 1,324 males (58.7%). The all-cause 30-d readmission rate was 7.1%. HRR was independently associated with 30-d readmission among the evaluated biomarkers, whereas SI and NLR showed no significant correlation. A non-linear relationship was found between HRR and readmission risk, with an inflection point at 0.94. Patients with HRR < 0.94 exhibited a significantly higher risk of readmission, whereas no significant association was found for HRR ≥ 0.94. Mediation analysis revealed that N-terminal pro-B-type natriuretic peptide (NT-proBNP) partially mediated this relationship, which accounted for 13.6% of the effect. Conclusions HRR is an independent predictor of all-cause 30-d readmission in patients with a non-linear relationship observed. An inverse association was found for HRR < 0.94, whereas no significant association was found for HRR ≥ 0.94. Additionally, NT-proBNP was identified as a partial mediator of this relationship.